1995
DOI: 10.1037/0022-0663.87.4.559
|View full text |Cite
|
Sign up to set email alerts
|

Interrelationship of knowledge, interest, and recall: Assessing a model of domain learning.

Abstract: Two experiments examined the interrelationship of subject-matter knowledge, interest, and recall in the field of human immunology/human biology and assessed cross-domain performance in the field of physics. Framed by a stage model of domain learning, cluster-analytic methods were used to group individuals on the basis of their performance on cognitive and affective measures in immunology. Resulting cluster profiles were compared with predictions expected from the stage model. Performance for students in these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
225
2
1

Year Published

1998
1998
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 300 publications
(242 citation statements)
references
References 67 publications
14
225
2
1
Order By: Relevance
“…Conceptual learning includes several types of acquisition consisting of particular features, propositions, and principles in a domain (Chi et al, 1994). Students at the highest level of conceptual learning acquire explanatory principles for phenomena and events (Alexander et al, 1996). This knowledge is active and not inert.…”
Section: Conceptual Themementioning
confidence: 99%
See 1 more Smart Citation
“…Conceptual learning includes several types of acquisition consisting of particular features, propositions, and principles in a domain (Chi et al, 1994). Students at the highest level of conceptual learning acquire explanatory principles for phenomena and events (Alexander et al, 1996). This knowledge is active and not inert.…”
Section: Conceptual Themementioning
confidence: 99%
“…For example, conceptual knowledge of a topic such as adaptation includes information about species, habitats, life cycles, and evolutionary change. Particular propositions about a species and its habitat are related to each other, and broad principles form a network of understanding (Alexander, Jetton, & Kulikowich, 1996;Chi et al, 1994). From our perspective, conceptual transfer occurs when the student uses conceptual knowledge to address a new question or to solve a problem.…”
mentioning
confidence: 99%
“…Participants are grouped based on the similarity of their composite scores, in our case according to their behavior on the eight course activity variables. Ward's procedure has shown to effectively recover the underlying structure of the data (Alexander et al 1995).…”
Section: Cluster Analysismentioning
confidence: 99%
“…The MDL posits that as an individual progresses from acclimation (the first stage of expertise in the MDL) to proficiency (the final stage of expertise the MDL) there are changes in both individuals" subject-matter knowledge and strategic processing. Empirical evidence using the MDL has suggested that there is an increase in both domain and topic knowledge through these stages of expertise development (e.g., Alexander, Jetton, & Kulikowich, 1995). Additionally, the MDL hypothesizes and empirical evidence has demonstrated that at acclimation the learner is relying primarily on surface-processing strategies, while individuals in proficiency rely primarily on deep-processing strategies (e.g., Alexander, 1997;Alexander et al, 2004).…”
Section: The Model Of Domain Learningmentioning
confidence: 99%